1970
DOI: 10.2466/pms.1970.31.3.739
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of Perceptual Organization and Orientation: Stochastic (Random) or Steady State (Satiation)?

Abstract: Using flat drawings, intra-reversal times were obtained for two kinds of fluctuations, perspective reversals in a figure eliciting apparent depth and reversals of lateral organization in a figure not eliciting apparent depth. The durations of the alternate percepts (P1 and P2) between reversals early in a viewing session were compared with recently published data of the same type. In the latter study, P1 was found to be of longer duration than P2, both with a flat drawing and a rotating skeletal cube. These pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1971
1971
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In either case, it could be concluded that spontaneous switching from horizontal to vertical motion was observed that was not attributable to differential changes in sensitivity for detectors responsive to features of the perceived versus the unperceived pattern. In the absence of differential adaptation as the cause for the reversal in the relative activation of the detectors associated with the perceived and unperceived motion, the horizontal-to-vertical switches observed in Experiment I are attributable to stochastic fluctuations in detector activation (DeMarco et aI., 1977;Hock et aI., 1993;Sadler & Mefferd, 1970;Taylor & Aldridge, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…In either case, it could be concluded that spontaneous switching from horizontal to vertical motion was observed that was not attributable to differential changes in sensitivity for detectors responsive to features of the perceived versus the unperceived pattern. In the absence of differential adaptation as the cause for the reversal in the relative activation of the detectors associated with the perceived and unperceived motion, the horizontal-to-vertical switches observed in Experiment I are attributable to stochastic fluctuations in detector activation (DeMarco et aI., 1977;Hock et aI., 1993;Sadler & Mefferd, 1970;Taylor & Aldridge, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…perience with a given figure, be it a flat drawing or a three-dimensional one, and regardless of the specific instructions or mean rate of fluct~iation (Mefferd, Wieland, Cook, Sadler, Benton, & Redding, 1966;Wieland & Mefferd, 1967;Mefferd, 1968aMefferd, , 1968bMefferd, , 1968cSadler & Mefferd, 1970). Porter (1938) also has commented on this extreme variation, and Donahue and Griffitts (1931) suggested that inspection of individual data was superior to examination of group means in light of such variability.…”
mentioning
confidence: 94%
“…Of course, there will be some "noise" or error variance within individuals as well, but this variation should be relatively small if indeed any single process (such as satiation) is exerting significant control over 0's perceptual experience. If individuals report highly erratic and unpredictable durations for each of two (or several) alternate percepts in a viewing session, we contend that fluctuations well may be based on an over-all stochastic rather than a satiation process (Sadler & Mefferd, 1970). In the absence of contrary evidence, we certainly are not justified in assuming that non-systematic intra-individual variability is due entirely to "noise" and as a consequence "smooth" it out by groupaveraging processes.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The part of the pattern reported most often as figure, or that seems to dominate the viewing, is defined as showing dominance. Several studies have attempted to obtain quantitative data on the factors responsible for determining dominance (Brown, 1955;Cohen, 1959;Goldhamer, 1934;Graham, 1929;Harrower, 1936;Oyama, 1950;Price, 1967;Sadler & Mefferd, 1970;Thetford, 1963). Some of the factors influencing figural dominance explored in these studies include hue, brightness, contrast with the surrounding background, and duration of observation time.…”
mentioning
confidence: 99%